CONTRIBUTION OF LEG MUSCLE EXPLOSIVE POWER AND HAND-EYE COORDINATION AGAINST UPPER SERVE CAPABILITY - Kholid, Abdul; Wijaya, Antony; Altaibi, Altaibi; Febrianto, Habibi; Nurmawati, Nurmawati (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2021)
The problem in this study is the low service ability of students of SMP Negeri 5 Rambah Hilir, and it is suspected that the problem arises due to several factors such as the low level of leg muscle explosive power and eye-hand coordination. This study aims to determine whether there is a contribution of leg muscle explosive power and eye-hand coordination to the top service ability of extracurricular students at SMP Negeri 5 Rambah Hilir. This research is included in correlational research. The population in this study were all extracurricular students at SMP Negeri 5 Rambah Hilir, totaling 15 people. From the research results it is known that the correlation coefficient rtitung > rtabel (hypothesis is accepted) and the significant test coefficient of the variables X1 - Y, X2 - Y and X1 X2 to Y obtained Fhitung > Ftabel. The results of this study prove: (1) there is a contribution between the X1 leg muscle explosive power variable to the upper service ability (Y) of 55.8%. (2) There is a contribution between the Eye-Hand Coordination variable (X2) to the Upper Service Capability (Y) of 66.2%. (3) Contribution of Leg Muscle Explosive Power (X1) and Eye-Hand Coordination (X2) to Upper Service Ability (Y) was 73.4%.